Innovative architecture design for high performance organic and hybrid multi-junction solar cells - Li, Ning; Spyropoulos, George D.; Brabec, Christoph (Proceedings Volume 10363,Organic, Hybrid, and Perovskite Photovoltaics XVIII, 2017)
The multi-junction concept is especially attractive for the photovoltaic (PV) research community owing to its potential to overcome the Schockley-Queisser limit of single-junction solar cells. Tremendous research interests are now focused on the development of high-performance absorbers and novel device architectures for emerging PV technologies, such as organic and perovskite PVs. It has been predicted that the multi-junction concept is able to boost the organic and perovskite PV technologies approaching the 20% and 30% benchmarks, respectively, showing a bright future of commercialization of the emerging PV technologies. In this contribution, we will demonstrate innovative architecture design for solution-processed, highly functional organic and hybrid multi-junction solar cells. A simple but elegant approach to fabricating organic and hybrid multi-junction solar cells will be introduced. By laminating single organic/hybrid solar cells together through an intermediate layer, the manufacturing cost and complexity of large-scale multi-junction solar cells can be significantly reduced. This smart approach to balancing the photocurrents as well as open circuit voltages in multi-junction solar cells will be demonstrated and discussed in detai